Chlamydia trachomatis genotypes in a cross-sectional study of urogenital samples from remote Northern and Central Australia. Issue 1 (6th January 2016) - Giffard, Philip M; Brenner, Nicole C; Tabrizi, Sepehr N; Garland, Suzanne M; Holt, Deborah C; Andersson, Patiyan; Lilliebridge, Rachael A; Tong, Steven Y C; Karimi, Mahdad; Boylan, Prudence; Ryder, Nathan; Johns, Tracy; et al.
Abstract : Objectives: The objective was to determine the frequency of trachoma genotypes of Chlamydia trachomatis- positive urogenital tract (UGT) specimens from remote areas of the Australian Northern Territory (NT). Setting: The setting was analysis of remnants of C. trachomatis positive primarily UGT specimens obtained in the course of clinical practice. The specimens were obtained from two pathology service providers. Participants: From 3356 C. trachomatis specimens collected during May 2012–April 2013, 439 were selected for genotyping, with a focus on specimens from postpubescent patients, in remote Aboriginal communities where ocular trachoma is potentially present. Primary and secondary outcome measures: The primary outcome measure was the proportion of successfully genotyped UGT specimens that were trachoma genotypes. The secondary outcome measures were the distribution of genotypes, and the frequencies of different classes of specimens able to be genotyped. Results: Zero of 217 successfully genotyped UGT specimens yielded trachoma genotypes (95% CI for frequency=0–0.017). For UGT specimens, the genotypes were E (41%), F (22%), D (21%) and K (7%), with J, H and G and mixed genotypes each at 1–4%. Four of the five genotyped eye swabs yielded trachoma genotype Ba, and the other genotype J. Two hundred twenty-two specimens (50.6%) were successfully genotyped. Urine specimens were less likely to be typable than vaginal swabs (p<0.0001). Conclusions: Unlike in some other studies, in the remote NT, trachoma genotypes of C. trachomatis were not found circulating in UGT specimens from 2012 to 2013. Therefore, C. trachomatis genotypes in UGT specimens from young children can be informative as to whether the organism has been acquired through sexual contact. We suggest inclusion of C. trachomatis genotyping in guidelines examining the source of sexually transmitted infections in young children in areas where trachoma genotypes may continue to circulate, and continued surveillance of UGT C. trachomatis genotypes.